Manajemen Perencanaan Dan Pelaksanaan Pendidikan Islam Di MTSN 5 Labuhanbatu - Mesiono, Mesiono; Fuadi, Wan Anwar; Fattah, Farihin Abdillah; Hirwansyah, Hirwansyah (ALACRITY : Journal of Education, 2024)
This study aims to describe the management of planning and implementation of Islamic education at MTsN 5 Labuhanbatu. As an Islamic educational institution, MTsN 5 Labuhanbatu carries out the educational process based on the applicable national education regulations and standards, such as Law Number 20 of 2003 concerning the National Education System, Government Regulation Number 19 of 2005 concerning National Education Standards, and Regulation of the Minister of Education and Culture Number 24 of 2016 concerning Content Standards for Primary and Secondary Education. The research method used is a case study with a qualitative approach, where the researcher conducts observations, data collection, information analysis, and in-depth reporting of results. The research results show that the planning management at MTsN 5 Labuhanbatu includes the development of curriculum, teaching materials, and the determination of learning strategies oriented towards the achievement of student competencies. Meanwhile, the implementation of Islamic education at MTsN 5 Labuhanbatu is carried out through the integration of Islamic values in the learning process, the habituation of noble character, and the strengthening of students' religious character. This research provides a comprehensive overview of the practice of planning and implementation management of Islamic education at MTsN 5 Labuhanbatu, which can be a reference for other Islamic education managers.